Acoustic Properties of Lanthanum-Samarium Phosphate Glasses - Hassan, Senin; Abd. Aziz, Sidek; G. A., Saunders (Universiti Putra Malaysia Press, 1995)
From measurements of changes in transit time of 10 MHz of ultrasonic waves as a function of temperature and hydrostatic pressure, the acoustic properties of (La203)x(Sm203)y(P20,,) (l-x-y) glasses with compositions near to that corresponding to the metaphosphate have been determined. For each glass, the second order elastic stiffness tensor components Cij ' (SOEC) continue to increase down to 10 Kin a manner consistent with phonon interactions with tVi'Qlevel systems. Measurements of the effects of hydrostatic pressure on the ultrasonic wave velocities have been used to determine the hydrostatic pressure derivatives (dCij/dP) T,P=O of the SOEC and (dBo'/ dP) T,P=O of the bulk modulus Bo at room temperature (293K). For these glasses, (dCll/dP), (dC44/dP), and (dBo / dP), are small but positive; the corresponding glasses stiffen under pressure. The elastic behaviour under pressure of these glasses lies intermediate between those of (Sm203)y(P20,,),(I_x) and (La20:1)y(P20,,) (I-x) glasses. Replacement of La3+ by Sm3+ in the temary phosphate glasses drives a slight acoustic mode softening. Possible. sources of the different effect of La:>+ and Sm3+ modifiers on the nonlinear acoustic properties of metaphosphate glasses are discussed.